2019
DOI: 10.1190/int-2018-0245.1
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional neural networks as aid in core lithofacies classification

Abstract: Artificial intelligence methods have a very wide range of applications. From speech recognition to self-driving cars, the development of modern deep-learning architectures is helping researchers to achieve new levels of accuracy in different fields. Although deep convolutional neural networks (CNNs) (a kind of deep-learning technique) have reached or surpassed human-level performance in image recognition tasks, little has been done to transport this new image classification technology to geoscientific problems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…As with WaveNet, this allows the network to consider context above and below the individual labels when making predictions-however, the sequences could not be as long, since image data is two orders of magnitude larger memory size than CCL per unit depth. Other researchers have used CNN models on carbonate core image data with success (Pires de Lima et al, 2019).…”
Section: Deep Ten For Use With Image Datamentioning
confidence: 99%
“…As with WaveNet, this allows the network to consider context above and below the individual labels when making predictions-however, the sequences could not be as long, since image data is two orders of magnitude larger memory size than CCL per unit depth. Other researchers have used CNN models on carbonate core image data with success (Pires de Lima et al, 2019).…”
Section: Deep Ten For Use With Image Datamentioning
confidence: 99%
“…Using several hundred feet of labeled core from a Mississippian limestone in Oklahoma (data from Suriamin andPranter, 2018 andPires de Lima et al, 2019), we selected a small sample of 285 images from five distinct lithofacies to be classified by the retrained CNN models. Pires de Lima et al (2019) describes how a sliding window is used to generate CNN input data, cropping small sections from a standard core image. We used 10% of the data as the test set and achieved an accuracy of 1.0 using the retrained MobileNetV2 and an accuracy of 0.97 using the retrained InceptionV3 (Table 1).…”
Section: Cnn-assisted Core Descriptionmentioning
confidence: 99%
“…The list of studies using transfer learning for the classification of geoscience images is also expanding. Examples include Pires de Lima et al [24], who used transfer learning for the classification of lithofacies using pictures of core data. In contrast to some of the examples cited, Baraboshkin et al [25] reported inferior performance when using transfer learning than when training a CNN model with randomly initialized weights.…”
Section: Introductionmentioning
confidence: 99%